Evaluation of the Influence of Ambient Temperature on the Performance of the Trans-Amadi Gas Turbine Plant - Emughiphel Nelson Igoma (Journal of Power and Energy Engineering, 2016)
This paper examines the effects of ambient temperature on the Trans-Amadi gas turbine power station Phase II. The investigation took thirteen (13) months (January 2012 to January 2013) during which plant data were monitored and operational Logsheets like turbine logsheets, plant—auxiliaries’ logsheets and generator logsheets were studied. The gas turbine (GT) that was under investigation was GT-2: MS5001 Nuovopignone with designed installed capacity of 25.0 Megawatts (MW). The result of the study shows that a 1˚C rise of the ambient temperature is responsible for the following: 0% - 0.12% decrease in the power output, 0% - 0.12% increase in the pow er differential, 0% - 1.17% decrease in the thermal efficiency, 0% - 27.18% increase in the heat rate and 0% - 3.57% increase in the specific fuel consumption. An ambient temperature of 30˚C is found to yield minimal fuel consumption.
Keywords: Ambient Temperature; Performance; Gas Turbine; Power and Thermal Efficiency